John E. Freund's mathematical statistics - Freund, John E. (Prentice Hall, 1999)
Intended for a two-semester or a three-quarter calculus-based Introduction to the Mathematics of Statistics course, this calculus-based introduction to the theory - and application - of statistics reflects the statistical thinking, the teaching of statistics, and practices - including the use of the computer.